Pelatihan Gerak Tari Lampung Karakter Putra pada Guru Seni Tari Se-Bandar Lampung - Susi Wendhaningsih; Dwiyana Habsary; Agung Kurniawan; Indra Bulan (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS LAMPUNG, 2022)
This activity explains more about kuttau and khakot dance in practical learning. This activity was created to improve the ability of dance teachers in learning a variety of dance movements in the men's character and to preserve culture, as well as to form a mindset or point of view towards male dancers. This service activity aims to provide training on men's character dance movements to dance teachers throughout Bandar Lampung. The output of this training activity is that dance teachers are able to teach a variety of dance movements of the son's character with good and correct techniques. The methods used in this devotion are the lecture method, demonstration method, practice method, and presentation method. This training activity was attended by 20 participants, namely dance teachers at the junior and senior high school levels in Bandar Lampung. The results of the trainees' achievements are in the